How Sustainable Is Private Equity? Unlocking the Impact of Private Equity on Asset-Level Sustainability: An Empirical Investigation - Paul Sunzenauer (Junior Management Science (JUMS), 2024)
The debate over the broader impact of the private equity industry has been a contentious topic in the academic literature. While recently, private equity investors have endorsed sustainability in their investment strategies, little is known whether the industry promotes sustainable transformation. This research uses data from the U.S. Environmental Protection Agency on the emission and handling of toxic chemicals in U.S. factories from 1991 to 2021 as a proxy for facility sustainability. The study reveals that, compared to the overall peer group facilities involved in a private equity takeover reduce pollution by 1.55 %-points less and reduce production waste by 1.1 %-points more in the two years after takeover. Further analysis indicates, that with a higher environmental hazard of the underlying chemicals, both the increase in pollution and the decrease in production waste become more pronounced. The study reveals that private equity ownership does not result in enhanced ecological sustainability. Further, the concurrence of the found trends with generally rising costs of both pollution control and raw materials of higher hazards suggest that the private equity business model is only effective in achieving sustainability goals if those are well aligned with financial objectives.
Keywords: 650; impact of private equity; private equity; SRI; sustainability; sustainable finance